Flexible "Arms" and Anion Recognition. Issue 17 (13th June 2017) - Robson, Ryan N.; Hay, Benjamin P.; Pfeffer, Frederick M.
Abstract: Fused [3]polynorbornanes functionalised with flexible ethylenethiourea "arms" were investigated as hosts for binding the structural isomers terephthalate and isophthalate. It was intuitively thought that the flexibility of the arms would ensure strong binding of both species. However, both solution and in‐silico experiments confirmed much stronger binding of isophthalate. Of interest, molecular modelling indicated that the arms possessed only limited flexibility. Counterintuitively this work indicates that this host, despite the flexible arms, is actually highly preorganised and adopts a remarkably similar structure when binding both guests and it is only the hydrogen bonding interactions that vary. Abstract : The role of "flexible arms" was examined using a bisthiourea host where each recognition group was attached to a rigid [3]polynorbornane framework by an ethylene spacer. Surprisingly, molecular modelling studies indicated that little adjustment in the "flexible arms" occurred at all and selectivity between two related guests was achieved primarily by changes in hydrogen bonding motifs.